Peran Guru Bimbingan Konseling Dalam Membentuk Moral Siswa Di SD Muhammadiyah 23 Semanggi Surakarta Tahun 2016/2017 - Erfina, Lina, Drs. Rubino Rubiyanto, M.Pd (2017)
This study aims to describe: (1) the role of the homeroom teacher in the implementation of guidance and counseling in forming the morals of students, (2) difficulties in mentation guidance in forming moral students, and (3) the solution of implementation constraints in forming moral students. This study includes a descriptive qualitative research. Techniques of collection data use interviews, observation and documentation. Analysis of data is used interactive analysis that includes data reduction, data presentation and conclusion. Mechanical examination of the validity of data is using triangulation. The results of the study showed (1) homeroom teacher has a very important role in forming moral students because there is no special guidance and counselingteachers in that school. Guidance and counseling play in forming the moral of students. Following the guidance,there will be student behavior change be better. Ways that are done to forming student behavior are with group guidance, individual counseling and f-development service, (2) the obstacles encountered in the implementation ofguidance and counseling, there are different aracteristics of students, the students' attention in the implementation ofguidance and counseling, the balance of the guidance and counseling at school and at home. (3) the solution is to approach with students, provide a special time for the implementation of the guidance, and cooperation with parents of students.